Regional Entrepreneurship System: Development Parameters and Potential of Reconfiguration - Solodilova, Natalya Zinovyevna; Malikov, Rustam Ilkamovich; Grishin, Konstantin Evgenyevich (Economy of Regions, 2017)
We article deals with the development of entrepreneurship in the Russian regions. Firstly, the state of both Russian entrepreneurship, in general, and small and medium-sized business in particular is not satisfactory. Secondly, the measures implemented by the state in the field of entrepreneurship development are not sufficiently effective. To the authors’ opinion, these two facts are due, among other things, to a lack of a holistic understanding of what constitutes an institution of entrepreneurship in a spatial context. The authors propose to consider the development of regional entrepreneurship using the system approach with the scope to the regional business system. Within the proposed authors’ approach, resources, economic agents and institutions are considered as the main elements of this system. We authors substantiate that there are institutional configurations, and not simple institutions, which determine the parameters of interaction between the elements of the regional enterprise system. These elements can contribute to the enterprise processes in the territory or block them. We assume that even a region with an essential resource of business potential is not able to realize it completely until it develops an effective institutional configuration of the regional business system. In order to investigate certain parameters of the institutional configuration of the regional business system, we propose a methodology for assessing the institutional loyalty of business entities and testing this technique on the example of eighty-four constituent entities of the Russian Federation. We have concluded that, in a large part of the Russian regions, a successful implementation of strategy for the development of small and medium-sized businesses will require the transformation of the regional enterprise system on the basis of reengineering. It involves a radical redesigning the entire system, ensuring the entrepreneurial processes in a territory. We authors prove that the basis for reengineering should be the institutional reconfiguration of the regional business system. We results of the research can be used to identify systemic problems that impede the development of entrepreneurship in the Russian regions and to develop more effective measures to address these problems.